PLA-HPG based coating enhanced anti-biofilm and wound healing of Shikonin in MRSA-infected burn wound - Han, Huiyu; Chen, Lianheng; Liang, Shu; Lü, Jiawei; Wu, Yashi; Wang, Xiongjun; Xu, Fei; Ge, Lanlan; Xiao, Lingyun (Frontiers in Bioengineering and Biotechnology, 2023)
Burn wounds are susceptible to bacterial infections, including Methicillin-resistant Staphylococcus aureus (MRSA), which typically form biofilms and exhibit drug resistance. They also have specific feature of abundant exudate, necessitating frequent drug administration. Shikonin (SKN) has been reported to reverse MRSA drug resistance and possesses anti-biofilm and wound healing properties, however, it suffers from drawbacks of low solubility and instability. In this study, we developed PLA-HPG based bioadhesive nanoparticles SKN/BNP, which demonstrated a drug loading capacity of about 3.6%, and exhibited sustained-release behavior of SKN. The aldehyde groups present on the surface of BNP improved the local adhesion of SKN/BNP both in vitro and in vivo, thereby reducing the frequency of drug dosing in exudate-rich burn wounds. BNP alone enhanced proliferation and migration of the fibroblast, while SKN/BNP promoted fibroblast proliferation and migration as well as angiogenesis. Due to its bioadhesive property, BNP directly interacted with biofilm and enhanced the efficacy of SKN against MRSA biofilm in vitro. In a mouse model of MRSA-infected burn wounds, SKN/BNP demonstrated improved anti-biofilm and wound healing efficiency. Overall, our findings suggest that SKN/BNP holds great promise as a novel and effective treatment option for clinical applications in MRSA-infected burn wounds.